PERUBAHAN LAMA PENYINARAN MATAHARI TAHUN 1990-2019 DI KALIMANTAN BARAT - Muhammad Elifant Yuggotomo; Evi Gusmayanti; Dadan Kusnandar (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
The sun is a source of renewable energy relating to climate change. Sunshine Duration (SD) is the element to an important indicator of the sun. West Kalimantan is located in the equator area receiving sunlight most of the year. This study aims to identify change in SD in West Kalimantan. The variable used is the average SD data from 1990 to 2019 divided into three time periods at five stations representing monsoon and equatorial rain patterns in West Kalimantan. ANOVA and Tukey tests are used for statistical analysis. The highest average SD is at Ketapang Station. The average annual SD in the monsoon region is higher than the equatorial region. In the dry season, the average monthly SD is higher than during the rainy season. There was an anomaly SD in the dry season in 1997 due to forest and land fires which corresponds to the El Nino event. The time period of the decade has a real effect on the average annual SD at Sambas and Supadio Pontianak Station. The average SD in 2010-2019 at Sambas Station and Supadio Pontianak Station was higher than the previous year's period. SD is an important factor for measuring solar energy, so the change shows good availability as a renewable energy source in West Kalimantan.